Conductive Co-based metal–organic framework nanowires: a competitive high-rate anode towards advanced Li-ion capacitors. Issue 43 (23rd October 2019) - Sun, Jinfeng; Guo, Lingzhi; Sun, Xuan; Zhang, Jinyang; Liu, Yang; Hou, Linrui; Yuan, Changzhou
Abstract : 1D conductive metal–organic framework Co3 (HHTP)2 nanowires with a high Li + diffusion coefficient are first explored as a promising high-rate anode for advanced Li-ion capacitors. Abstract : Conductive Co3 (HHTP)2 nanowires are firstly demonstrated as a high-rate anode with a reversible capacity of 435 mA h g −1 at 1.0 A g −1 for hybrid Li-ion capacitors (LICs). Besides, the Co3 (HHTP)2 -based LIC displays an encouraging energy density of 64 W h kg −1 at a superb power density of 10 kW kg −1 .